2018
DOI: 10.1111/jfb.13798
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic investigation of appetite‐regulation and digestive processes in giant grouper Epinephelus lanceolatus during early larval development

Abstract: The giant grouper Epinephelus lanceolatus is an ecologically vulnerable species with high market demand. However, efforts to improve larval husbandry are hindered by a lack of knowledge surrounding larval developmental physiology. To address this shortfall, a transcriptomic approach was applied to larvae between 1 and 14 days post hatch (dph) to characterise the molecular ontogenesis of genes that influence appetite and digestion. Appetite regulating factors were detected from 1 dph, including neuropeptide Y, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…In goldfish and zebrafish, Y1 antagonist BIBP3226 icv inhibits the orexigenic effects of NPY ( 16 , 192 ). ICV injection of Y1 agonist (Leu31, Pro34)-NPY and Y5 agonist (D-32Trp)-NPY promoted the food intake in goldfish, but neither the Y2 agonist NPY ( 2 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) nor the (Pro13, Tyr36)-NPY ( 13 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) has significant effect on feeding behaviors, suggesting that NPY receptors similar to mammalian Y1 and Y5 may be involved in feeding regulation in teleost ( 235 , 236 ). On the other hand, in rainbow trout, ICV injection of both the Y1 agonist (Leu31, Pro34)-NPY and the Y2 agonist NPY ( 3 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) stimulated food intake ( 208 ).…”
Section: Neuropeptide Y and Somatostatin In Food Intake And Growth Of...mentioning
confidence: 99%
See 3 more Smart Citations
“…In goldfish and zebrafish, Y1 antagonist BIBP3226 icv inhibits the orexigenic effects of NPY ( 16 , 192 ). ICV injection of Y1 agonist (Leu31, Pro34)-NPY and Y5 agonist (D-32Trp)-NPY promoted the food intake in goldfish, but neither the Y2 agonist NPY ( 2 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) nor the (Pro13, Tyr36)-NPY ( 13 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) has significant effect on feeding behaviors, suggesting that NPY receptors similar to mammalian Y1 and Y5 may be involved in feeding regulation in teleost ( 235 , 236 ). On the other hand, in rainbow trout, ICV injection of both the Y1 agonist (Leu31, Pro34)-NPY and the Y2 agonist NPY ( 3 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) stimulated food intake ( 208 ).…”
Section: Neuropeptide Y and Somatostatin In Food Intake And Growth Of...mentioning
confidence: 99%
“…ICV injection of Y1 agonist (Leu31, Pro34)-NPY and Y5 agonist (D-32Trp)-NPY promoted the food intake in goldfish, but neither the Y2 agonist NPY ( 2 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) nor the (Pro13, Tyr36)-NPY ( 13 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) has significant effect on feeding behaviors, suggesting that NPY receptors similar to mammalian Y1 and Y5 may be involved in feeding regulation in teleost ( 235 , 236 ). On the other hand, in rainbow trout, ICV injection of both the Y1 agonist (Leu31, Pro34)-NPY and the Y2 agonist NPY ( 3 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) stimulated food intake ( 208 ). Recently, it is reported that ICV injection of Y1 agonist (Leu31, Pro34)-NPY and Y2 agonist NPY ( 13 24 , 27 29 , 31 , 53 , 65 , 79 , 80 , 83 85 ) both increased the appetite of Siberian sturgeon within 30 min ( 228 ).…”
Section: Neuropeptide Y and Somatostatin In Food Intake And Growth Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Anderson et al . () used a transcriptomic approach to explore molecular processes that underpin development of appetite, feeding and digestion in E. lanceolatus larvae. They focussed on the first two weeks of life, a critical period for larval husbandry during which the larvae first open their mouth and start exogenous feeding.…”
mentioning
confidence: 99%